1969
DOI: 10.1039/c2969001187a
|View full text |Cite
|
Sign up to set email alerts
|

The preparation and structure of pentathiazyl tetrachloroaluminate, S5N5AlCl4

Abstract: The preparation of a stable salt of the pentathiazyl ion, S5N5+, is described; the ion has been shown by X-ray diffraction to be a planar, heart-shaped ring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1972
1972
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Self consistency could only be achieved for structures corresponding to the formulae la and ld-lf. [3,4]. Even the S-N-S bond angles of 177° around the tip of the heart of le found [3] are reproduced in the calculations.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…Self consistency could only be achieved for structures corresponding to the formulae la and ld-lf. [3,4]. Even the S-N-S bond angles of 177° around the tip of the heart of le found [3] are reproduced in the calculations.…”
supporting
confidence: 56%
“…This led us to compute the energies of the isomers 1 a to 1 f shown below. It was found that the two species of lowest energy were those with the heart shaped structure, 1 e, and the azulene like structure, If, whose structural parameters have been reported recently from X-ray investigations [3,4]. To our surprise the energy difference calculated between both isomers (le and I f) was found to be 2 eV, a difference rather large for two conformational isomers occuring in Nature.…”
mentioning
confidence: 77%
“…In In(Ph)3, bonds from the metal to the a carbon of phenyl groups on two neighboring molecules together with three planar In-C bonds again result in a coordination number of five.5 These conclusions, and the present structure, are in agreement with results for InX3 (X = halide or pseudohalide) species, where the three-coordinate monomer readily undergoes dimerization or adduct formation to give coordination numbers of four, five, or six. 4 The electron deficiency is however apparently unique to the three organoindium compounds in this context. It may be that this can be regarded as a type of electron donation in which the donor is not in its ground state, as is usually assumed for (say) a pyridine adduct, but in some electronically excited state.…”
Section: Structure Description and Discussionmentioning
confidence: 95%
“…The first stable and characterized chalcogen–pentele cluster was found in 1969 as the heart‐shaped ring (S 5 N 5 ) + , which was obtained from trithiazylchloride in organic solvents and isolated as the chloridoaluminate1 or the chloridogallate 2. A decade later, the cage‐shaped ions (As 3 Se 4 ) + and (As 3 S 4 ) + were synthesized from As 4 S 4 and As/Se melts, and the dissolved polycationic species were obtained from sulfur and selenium and AsF 5 and SbF 5 in liquid SO 2 3.…”
Section: Introductionmentioning
confidence: 99%